2013
DOI: 10.1016/j.micromeso.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Aerogel and xerogel WO3/ZrO2 samples for fine chemicals production

Abstract: a b s t r a c t WO 3 /ZrO 2 systems were prepared by sol-gel technique using different procedures for the solvent extraction: evaporation in vacuum at room temperature (xerogel) and extraction in supercritical conditions (aerogel). Two reactions of industrial interest were investigated under mild conditions: (i) acylation of veratrole with acetic anhydride; (ii) acylation of anisole with benzoic anhydride. Several techniques were employed in order to study the influence of the synthetic parameters on texture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The isotherm of SO 4 2− /ZrO 2 in Fig. 3(b) contained a hysteresis loop in the P / P 0 range from 0.4 to 0.8, which confirmed the presence of mesopores in the sample 52 . The BET specific surface area of SO 4 2− /ZrO 2 was only 87 m 2 g −1 , and the average pore diameter was 3.2 nm (Table 1).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The isotherm of SO 4 2− /ZrO 2 in Fig. 3(b) contained a hysteresis loop in the P / P 0 range from 0.4 to 0.8, which confirmed the presence of mesopores in the sample 52 . The BET specific surface area of SO 4 2− /ZrO 2 was only 87 m 2 g −1 , and the average pore diameter was 3.2 nm (Table 1).…”
Section: Resultsmentioning
confidence: 64%
“…3(b) contained a hysteresis loop in the P/P 0 range from 0.4 to 0.8, which confirmed the presence of mesopores in the sample. 52 The BET specific surface area of SO 4 2− /ZrO 2 was only 87 m 2 g −1 , and the average pore diameter was 3.2 nm ( Table 1). The SO 4 2− /ZrO 2 sample was prepared by calcining UiO-66 after impregnation with ammonium sulfate solution.…”
Section: Nitrogen Bet Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Such catalysts have been prepared by sol-gel method and dried either in supercritical condition of solvents or in ordinary condition [4][5][6][7][8][9] since sol-gel route offers a better control of the homogeneity of the prepared solids as regards to other methods [10][11][12]. For zirconia based catalysts, the sol-gel method offered the opportunity to introduce in one step zirconium alkoxide, metal precursor and sulfate groups as dopant in order to assure the homogeneity and to control morphological and textural properties of the final materials [13,14].The obtained results showed that aerogels manifest developed textural properties as well as higher acidity.…”
Section: Introductionmentioning
confidence: 99%
“…This confirms the XRD results, which suggested that the gallium is dispersed on the surface, as metallic gallium and in the oxide form, which may be favorable for complete oxidation to occur on the surface of these materials. 23,24 XPS analysis of the surface of the catalysts was carried out to determine the percentage of Ga 2 O 3 on the surface of the catalysts. Interestingly, the catalyst MS-Ga7% presented a higher amount of Ga 2 O 3 on the surface of the material compared to MS-Ga11%.…”
mentioning
confidence: 99%